CORRESPONDENCE BETWEEN PERSONALITY AND JOB TITLE - Tirso Javier Hernandez Gracia; Enrique Martinez Munoz; Lourdes Garcia Vargas; Alejandra Corichi Garcia; Jose Francisco Hernandez Gracia (European Scientific Journal, ESJ, 2015)
Does the position held by an individual in a company fit into his/her personality? The answer to this question is yes. This is because there is significant relationship between the characteristics possessed by a worker which includes his character, personality and way of life, with the current position he/she is holding in an organization. The evolution of man is in accordance with technological advancement, new cultures, social and economic developments, among other phenomena. In other words, the success in the position given to a person will depend largely on his/her personality from a mental and physical point of view. This aim of this paper is to analyze the part of clinical psychology which is associated with human talent through a series of characteristics and personality traits. Personality traits and characteristics are crucial for the proper performance of a worker in a specific job.